Optimization of scotta as growth medium to preserve biodiversity and maximise bacterial cells concentration of natural starter cultures for Pecorino Romano PDO cheese. Issue 14 (21st July 2020) - Chessa, Luigi; Paba, Antonio; Daga, Elisabetta; Caredda, Marco; Comunian, Roberta
ABSTRACT: Preservation of cheese microbiota biodiversity is central to the sensory quality of traditional and PDO cheeses. Lyophilized commercial selected starters, being advantageous in terms of cells concentration, are supplanting natural cultures causing important loss of microbial biodiversity in the dairy environment. Biodiversity could be recovered using natural starter cultures, however their cells concentration after propagation is lower than the commercial ones. Two autochthonous and biodiverse starter cultures (MixA and MixB) coming from scotta (residual whey from Ricotta cheese manufacture), collected in the 1960 s from Pecorino Romano PDO cheese manufactures, were revitalized in reconstituted commercial powder scotta . The aim of this study was the propagation of the microbial starter mixes increasing their bacterial concentration in the pellet, reducing nonessential scotta components by a fast and not-expensive method, without changing the microbial community balance. The behaviour of each mix inoculated in scotta was compared to that in half-concentrated, clarified, and half-concentrated-clarified scotta . Higher cells concentration in the pellets from the modified scotta was obtained, without changing technological performances and microbial fingerprint. The pellets obtained were reinoculated in commercial scotta for the preparation of the scotta-innesto (the typical starter for Pecorino Romano), and no differences were observed among the treatments after incubation. The reduction of nonessential scotta's components could help the reproduction of natural starter cultures preserving their properties. Abstract : The modified scotta, removing non-essential components, could be a fast and not-expensive method to reproduce natural starter cultures with high cells concentration, without affecting their technological performances and microbial balance.